Qualitative and Quantitative Estimation of Total Phenols in Narcissus tazettaL. Bulbs - Ali, Ola Kareem; Abdul-Kareem Tawfiq, Arwa; Yaseen Mohammed Hasan, Zainab (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Narcissus tazetta, a member of the Amaryllidaceae family, is known to be rich in bioactive metabolites such as alkaloids, phenolics and flavonoids, which have been found in nearly every species in this family. N. tazetta cultivated in Iraq, had not previously been studied for its active components; thus, the current study used phytochemical screening and phenolic compounds estimation, both qualitatively and quantitatively. Results showed that the plant alcoholic extract was rich in alkaloids, polyphenols and flavonoids besides tannins, polysaccharides and saponins. Qualitatively; TLC and HPLC chromatogram for total phenolics and flavonoids compounds revealed the presence of Gallic acid (GA), Caffeic acid (CA), Paracumarin acid (P-c), Chlorogenic acid (Ch), Catechin (Ca), Hydroqunolinon (H) with more abundant content in Vanillic and Salycilic acids as phenolic compounds; beside, Rutin (R), Quercetin (Q), Apegenin (Ap), Luetolin (L), and Kaempferol (K) as flavonoids. Dried bulbs of N. tazetta contain total phenolic compounds reached 90 mg/g and total flavonoids in a quantity of 0.47 mg/g. Plant bulb analyzed by colorimetric reaction assay.